Rapid one pot synthesis of mesoporous ceria nanoparticles by sol-gel method for enhanced CO2 capture - Azmi, A. A.; Ngadi, Norzita; Kamaruddin, M. J.; Zakaria, Z. Y.; Teh, Lee Peng; Annuar, N. H. R.; Herma Dina, Setiabudi; Jalil, A. A.; Aziz, M. A. A. (AIDIC, 2019)
The capture and storage of CO2 have been suggested as an effective strategy to reduce the global emissions of greenhouse gases. Hence, many studies have been carried out to develop highly efficient materials for capturing CO2. Herein, the CO2 capture performance of mesoporous ceria nanoparticle (MCN) was described. The MCN was synthesized under mild conditions through a sol-gel method using hexadecyltrimethylammonium bromide (CTAB) as a surfactant and further undergone a calcination process at 673 K for 3 h. The prepared MCN possess high surface area (76.0 m2 g -1 ) which is around 9-fold higher than that of commercial CeO2 (8.7 m2 g -1 ), indicating that the organic modification using CTAB is an effective way of preparing a porous structure. The MCN exhibited high CO2 uptake of 213.8 μmol g -1 at 298 K and 1 bar. The prepared MCN using sol gel has shown a rapid and cost-effective method compared to the hydrothermal method.